(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the problem of professional deformation among primary school teachers, its causes and impact on pedagogical activity. Also, the importance of pedagogical erudition in ensuring the professional stability of the teacher and preventing deformation processes is scientifically highlighted. During the study, pedagogical, psychological and methodological sources were analyzed, and the competencies necessary for the professional development of teachers working in the primary education system were identified. The results show that pedagogical erudition develops the reflexive activity of the teacher, reduces the risk of professional deformation, and increases the effectiveness of the educational process.